2012
DOI: 10.1109/tvcg.2010.269
|View full text |Cite
|
Sign up to set email alerts
|

Graph Drawing Aesthetics—Created by Users, Not Algorithms

Abstract: Prior empirical work on layout aesthetics for graph drawing algorithms has concentrated on the interpretation of existing graph drawings. We report on experiments which focus on the creation and layout of graph drawings: participants were asked to draw graphs based on adjacency lists, and to lay them out "nicely." Two interaction methods were used for creating the drawings: a sketch interface which allows for easy, natural hand movements, and a formal point-and-click interface similar to a typical graph editin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 12 publications
2
57
0
Order By: Relevance
“…Means in boxes indicate best actual mean rank for that contest. [34,30] and is supported by the positive correlations seen in the "# Outer trees" column in Table 1; R2 users create "aesthetic bend points" we observed, in contrast to previous research, while bends overall were correlated with a poor ranking, nevertheless, certain bend points serving an obvious (to us) aesthetic purpose were present in most of the top-ranked human layouts. This is true for all except Graph 4 in the 'Human 1st' column of Fig.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Means in boxes indicate best actual mean rank for that contest. [34,30] and is supported by the positive correlations seen in the "# Outer trees" column in Table 1; R2 users create "aesthetic bend points" we observed, in contrast to previous research, while bends overall were correlated with a poor ranking, nevertheless, certain bend points serving an obvious (to us) aesthetic purpose were present in most of the top-ranked human layouts. This is true for all except Graph 4 in the 'Human 1st' column of Fig.…”
Section: Resultssupporting
confidence: 78%
“…Most recently Purchase et al [30] asked participants to draw a graph specified by an adjacency matrix using a graph drawing sketch tool. They found that edge crossings were avoided and that grid-like layouts were preferred.…”
Section: Human Studies Considering Network Layoutmentioning
confidence: 99%
See 3 more Smart Citations